Munkanélküliség Debrecenben, különös tekintettel a tartósan állományon kívüliek helyzetére - Diebel, Andrea (Tér és Társadalom, 1996)
It is known that long term unemployment is an extremely dangerous situation, as it can stabilise after a certain period of time. During the time spent without a job, individuals suffer serious professional and psychical losses. They lose their professional experience, skills, which decreases their chances to find new jobs. Failures lead to crises of the self-image: Their self-confidence weakens, they lose hope and, due to these, they do not event try to find a job after a while. As the period of unemployment increases, most of the people eliminate their external connections and even their inner family ties often get loose and decline. The most frequent reasons for eliminating the external connections is the feeling of shame because of being unemployed, and also the fact that the conditions necessary to maintain social connections are not given. I examined the system of the inner family connections with respect to the development of the connection between the spouses and that of the parents with their children. The most common reasons triggering spouse conflicts are the changes in the financial conditions, the crisis of the self-image, alcoholism and the division of household jobs. Unemployment has a very complex effect on the connection between the parents and the children, too, which can strongly determine the future of the latter.